Human chorionic gonadotropin: Unknown about known - Borisova, M. A.; Moiseenko, D. Yu; Smirnova, Olga V. (Human Physiology, 2017)
The last two decade discoveries shift the accent from the consideration of human chorionic gonadotropin (hCG) as a hormone that controls progesterone production by corpus luteum cells to a powerful paracrine regulator that, in the tandem with its hyperglycosylated analog (h-hCG), induces successful implantation and coordinated dialog between blastocyst and uterine tissues. The ability of hCG and h-hCG to interact with TSH receptor and TGF-beta-RII, respectively, significantly extend the spectrum of processes controlled by these molecules. Differences between intracellular pathways of signal transduction between hCG and LH mediated by the same receptor (LH/hCG-R) impugn the unity of their effector mechanisms, which was previously considered as obvious. The paracrine properties of hCG include the control of fusion of trophoblasts into syncytiotrophoblasts, angiogenesis, immunity regulation, and endometrium predisposition to implantation. Angiogenesis is associated with LH/hCG-R expressed on mural cells of uterine spiral arteries as well as induced secretion of soluble VEGF form by endometrial cells. hCG regulates the ratio between different types of T-helper cells in maternal organism at the initial gestation stage determining a high level of Th2 cells. hCG supports local immunotolerance, functioning as a chemoattractant for T-suppressors (T-Treg) and an apoptotic factor for T-lymphocytes. Endometrial susceptibility arises from the activation of osteopantin secretion and the decline of mucin secretion by epithelial cells. h-hCG affects the same tissues as hCG, functioning as a paracrine agent regulating multiple cascades of cytokines. h-hCG plays the key role in the trophoblast invasion into the uterine decidua as a result of gelatinase secretion by these cells. The degree of the angiogenic effect of h-hCG is compatible with that of hCG, but its signal transduction is mediated by the TGF-beta signal transduction pathway that stimulates mural cell proliferation. h-hCG acts as a mitogen on NK-cells and is able to activate them and direct to angiogenesis maintenance. In this article, we attempted to elucidate the most important discoveries about the role of hCG and its hyperglycosylated analog, both accomplished and still upcoming.
CRIS-Team Scopus Importer:2023-04-20
Keywords: human chorionic gonadotropin; hyperglycosylated human chorionic gonadotropin; immunotolerance; implantation; trophoblast